Belgian Carriers of Rare ABCA7 Mutations Present with Pronounced Cerebral Amyloid Angiopathy and Alzheimer's Disease. (20th December 2022) - de Craen, Elisabeth Henndrickx Van; Bossaerts, Liene; Sieben, Anne; Loos, Caroline; Yperzeele, Laetitia; Engelborghs, Sebastiaan; De Deyn, Peter Paul; Van Broeckhoven, Christine
Abstract: Background: ABCA7 is a major risk gene for Alzheimer's disease (AD) and rare premature termination codon (PTC) and missense mutations are enriched in AD patients. In preliminary studies we obtained that ABCA7 PTC and missense mutation carriers present with a classic AD phenotype, but severe levels of cerebral amyloid angiopathy (CAA) were also found (table 1, figures 1‐2). We aim to delineate the clinicopathological phenotype of rare ABCA7 mutation carriers in Belgian CAA patients. Methods: Genetic screening of ABCA7 in a Belgian CAA cohort (n = 83), with genotype‐phenotype comparison of the ABCA7 carriers using demographics and clinicopathology data. Results: In 21.4% (18/84) of CAA patients a rare ABCA7 mutation was identified. Seven patients carried a PTC mutation, 10 a rare missense variant, and in one CAA patient we found a deletion. The mean onset age was 66.4±12.8 (range 47‐84) years, while the mean age at death was 68.0±10.3 (range 48‐92) years. In 87.5% (7/8) of patients a positive family history of disease was mentioned. Cognitive decline was present in 52.9% (9/17). Nine patients were diagnosed as probable CAA, and four as possible CAA. In six patients postmortem examination showed moderate‐to‐severe levels of CAA in all but one patient (83.3%, 5/6) and AD neuropathological hallmarks (100%, 6/6). Extensive levels of CAA were present in both the meningeal and capillary blood vessels, and moderate to high levels of CAA in the parenchymal blood vessels (Figure 3). Conclusions: Our data suggests that rare ABCA7 mutations are frequently present in CAA patients. Carriers show signs of severe levels of CAA, as well as AD neuropathological hallmarks. The findings of this study have important implications for future research and clinical practice.